TOP ELECTRODE INVESTIGATION OF OPV MODULES BASED ON P3HT:PC[60]BM FABRICATED VIA ROLL-TO-ROLL PROCESS - Miranda, Bárbara Hellen Souza; Rodrigues, Jair Francisco; Vilaça, Rodrigo; Bagnis, Diego (Revista Brasileira de Energia Solar, 2023)
Solar photovoltaic (PV) cells allow the direct conversion of sunlight into electricity without CO2 emission. Finding a way to cheaply utilize the vast amount of solar energy is one of the biggest challenges for this technology. The organic photovoltaic cells (OPV) are based on solution-processed photoactive polymers and can be fabricated via roll-to-roll (R2R) processes, which allow high production throughput with low costs. CSEM Brasil is building the foundations of future high-tech industries in Brazil and one of our key technology development areas is OPV modules production using R2R coating. In this work, polymer solar cells based on P3HT: PC[60]BM were prepared by R2R coating (electron transport, active and hole transport layers – ETL, AL and HTL) and by screen printing (top silver electrode). In order to save material and give more transparency of the OPV module were compared and evaluated the performance of two different suppliers of Ag paste (A and B) in three different top contact configurations, solid, grid and honeycomb. Additionally, were compared two different screen suppliers (I and II) for screen printing process and the Ag paste drying time studied. The comparisons were made with modules with an active area of 21.6 cm2 (6 stripes serially connected). Photovoltaic performance was evaluated in terms of Ag paste and screens suppliers, Ag pattern and drying time. Finally, modules were encapsulated in a R2R laminator using a flexible barrier film and evaluated in terms of lifetime.